Konsep Pendidikan Karakter dalam Perspektif Al-Qur'an: Analisis Tematik Surat Luqman Ayat 12-19 - Za’far Siddik, Rasyid; Fuad Ruhiyat, Ahmad; Athoillah Yusuf, Ibnu; Sulaeman, Rudi; Sofian (Hawari: Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
Moral crisis and character degradation among the younger generation in the digital era pose a serious challenge to the education world, which has predominantly focused on cognitive aspects. This research aims to explore the ideal concept of character education through a thematic analysis of Surah Luqman verses 12-19. Employing a qualitative research method with a library research approach and the "maudhu’i" (thematic) exegesis technique, this study dissects the exhortations of Luqman Al-Hakim as a comprehensive character curriculum. The research findings indicate that character education in the Qur'an is built upon four main pillars: the theological pillar (monotheism/tawhid and gratitude), the domestic pillar (filial piety), the integrity pillar (worship and "muraqabah"/God-consciousness), and the social ethics pillar (etiquette and communication). The study concludes that tawhid is the fundamental basis that drives all ethical human behavior; therefore, character education cannot be separated from the spiritual dimension.